Crafting gongs in two Ifugao communities in Northern Philippines - Montano, Lilymae Franco (2008)
This thesis presents a study of the flat gong tradition of the municipalities of Hingyon and Banaue in the province of Ifugao in the Cordillera Region of Northern Philippines.